Translation, transcultural adaptation, and validation of the Serbian version of the University of Washington Quality of Life (UW-QoL) Questionnaire – a pilot study - Stanisšić, Dragana; Daković, Dragana; Kozomara, Ružica; Mladenović, Raša; Mijailović, Sara; Djurdjević, Milica; Jovanović, Dejan; Vujović, Sanja (Vojnosanitetski pregled, 2024)
Background/Aim. The University of Washington Quality of Life (UW-QoL) questionnaire is one of the most frequently applied instruments for the evaluation of the health-related quality of life of head and neck cancer patients worldwide. The aim of this study was to perform a formal translation of the original version into the Serbian language, assess its psychometric properties, and validate it for use in the Serbian-speaking population. Methods. The study was designed as pilot research and conducted between August and October 2023. The internal consistency of the questionnaire was established by calculating Cronbach’s alpha coefficient (CA). The intraclass correlation coefficient (ICC) was a measure of temporal stability. The construct validity of the instrument was assessed by correlating its total scores with Oral Health Impact Profile-14 (OHIP-14) and Emotion Regulation Questionnaire results. Results. A total of 30 patients (23 males and 7 females) with a mean age of 58.07 ± 13.59 years were enrolled in the research. Mean values of the physical function and social-emotional function subscales were 59.50 ± 12.68 and 55.39 ± 15.26 (the researchers interviewed the participants) and 58.78 ± 12.57 and 57.72 ± 14.91 (the patients completed the questionnaire by themselves). CA value of the Serbian version of the UW-QoL questionnaire was 0.816 (the questionnaire was filled out by the researchers) and 0.802 (the subjects completed it on their own). ICC was 0.797. There was a statistically significant strong correlation between the UW-QoL questionnaire and OHIP-14 total scores. The obtained results showed a weak, non-significant correlation between the UW-QoL questionnaire and the Emotion Regulation Questionnaire. Conclusion. Our pilot research showed that the Serbian version of the UW-QoL questionnaire appears as psychometrically valid and reliable as the original English version.